Perancangan Sistem Informasi Surat Desa Berbasis Web Di Desa Terbangiang Kecamatan Bandar Petalangan Kabupaten Pelalawan - .BR, Mashdarul; Dahliyusmanto, Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Village letter creation is one form of village government service to the village residents. Village letter creation in Terbangiang Village is made by village residents that would visit the village office during working hours, then village officials would make a letter using Microsoft Word. Village letter creation in Terbangiang Village are still not optimal due to the relatively long service time, no standard format for making letters, poor administrative records, and writing errors. In order to maximize the letter creation service at the Terbangiang Village, an information system was created that helps residents and village officials in making letters. The information system make any village residents can submit letters online and receive notification via SMS when the letter is completed, village officials can approve and make letters without writing resident's data. System development is carried out using the waterfall method and is built using the CodeIgniter framework and is equipped with an SMS Gateway feature. The results of this research is an information system that makes it easier for residents and village officials to make village letters. Keywords: village letter, administration, web